Strategi Pendidikan Pranatal dalam Evolusi Perkembangan Anak - Ahmad Saifudin (Asosiasi Dosen Tarbiyah STAI Darussalam Nganjuk, 2020)
Humans as homo divinans/Godly creatures are also often referred to as homo religious/ religious creatures. In evolutionary terms, the basic abilities that cause humans to become divine beings are because in the human soul there is a religious instinct which is a natural literary religion, meaning that the process of development is highly dependent on the efforts of an educator, as is the case with other roles of reason. Without an instinctual education process, the child will not be able to develop optimally. Hence religious education is absolutely necessary to develop this instinctual power. Skeptical analysis that is not absolute, and can be one reason how important education is in human life in evolutionary ways. The changes that occur slowly but surely through an enculturation process or the inheritance of human cultural values as creatures who will always make changes both in the social and cultural fields, this effort is made in order to achieve maximum development. Children are the main object in education. Likewise the concept of prenatal education is a period of inculcating exemplary values ​​and habituation in children through parental behavior. Any behavior will easily be reflected in the child's personality at birth. This will be reflected in either the actions of the parents when the child is still in the womb or is already born, it also affects the psychological development of the child. So parents must always try to maintain their behavior and attitudes in order to remain relevant to religious norms, as an effort to get educated and qualified children both physically and mentally